Implementasi Nilai-Nilai Gotong-Royong dan Peduli Sosial pada Tradisi Nyadran (Studi Kasus di Dukuh Wonorejo, Desa Bulusan, Kecamatan Karangdowo,Kabupaten Klaten Tahun 2015) - Aryana, Mifta Yoga (2016)
This research aims to discription implementation, constraints and efforts in the implementation of the values and social care royong Nyadran in village of Wonorejo, Bulusan, Karangdowo, Klaten Regency. Data collection on this research with interviews, observation, and documents. Technique of data analysis by applying interactive models through data collection, reduction, withdrawal, and presentation of conclusions. Test the validity of the data in this study by means of triangulation techniques and sources. The results of this research show that: 1) implementation of the values and social care royong Nyadran in village of Wonorejo, Bulusan, Karangdowo, Klaten was jointly improve and clean up the Tomb without any coercion, sharing snacks prepared, appreciate the difference of gender, age, social status and religion. 2) constraint in the implementation of the values and social care royong Nyadran in village of Wonorejo, Bulusan, Karangdowo, Klaten Regency is less compact in the workplace Act, not to participate in a program of work, do not pay dues and are not set up hawker who eat together after the reading of the prayer event. 3) constraints in implementation efforts of the values of social care and royong Nyadran in village of Wonorejo, Bulusan, Kecamatan Karangdowo, Klaten Regency is the Head which gives instructions and guidance to each representative of the RT in order to carry out its task properly so that the implementation of the Nyadran went smoothly. Followed by the Chairman of Rt which collects the father and youth to work together on a program of work in intercultural awareness, Nyadran citizens for mutual reminding each other.